N‐Heterocyclic Carbene Catalyzed [4+2] Annulation of Enals via a Double Vinylogous Michael Addition: Asymmetric Synthesis of 3,5‐Diaryl Cyclohexenones - Chen, Xiang‐Yu; Liu, Qiang; Chauhan, Pankaj; Li, Sun; Peuronen, Anssi; Rissanen, Kari; Jafari, Ehsan; Enders, Dieter (Angewandte Chemie International Edition, 2017)
A strategy for the N‐heterocyclic carbene (NHC) catalyzed asymmetric synthesis of 3,5‐diaryl substituted cyclohexenones has been developed via oxidative [4+2] annulation of enals and alkenylisoxazoles. It is the first example of using NHC organocatalysis in a double vinylogous Michael type reaction, a challenging but highly desirable topic. This unprecedented protocol affords good yields as well as high to excellent diastereo‐ and enantioselectivities. N‐heterocyclic carbene organocatalysis allows the [4+2] annulation of enals with electron‐deficient 2,4‐dienes via a double vinylogous Michael addition sequence. The corresponding 3,5‐diaryl cyclohexenones are obtained in good to excellent yields with high to excellent diastereo‐ and enantioselectivities.